Murid baru di kelasku (The new student in my class) / Arlinah I Rahardjo ; ilustrator Melissa Goentoro, Risa Ambarizky - ARLINAH I RAHARDJO; Melissa Goentoro; Risa Ambarizky (Rainbow, 2013)
80 hlm. : ilus. ; 23 cm